2012
DOI: 10.1007/s00248-011-9997-2
|View full text |Cite
|
Sign up to set email alerts
|

First Prokaryotic Biodiversity Assessment Using Molecular Techniques of an Acidic River in Neuquén, Argentina

Abstract: Two acidic hot springs close to the crater of Copahue Volcano (Neuquén, Argentina) are the source of the Río Agrio. The river runs several kilometres before flowing into Caviahue Lake. Along the river, temperature, iron, other metal and proton concentrations decrease gradually with distance downstream. From the source to the lake and depending on the season, pH can rise from 1.0 (or even less) to about 4.0, while temperature values decrease from 70°C to 15°C. Water samples were taken from different stations on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 47 publications
(53 reference statements)
0
31
0
Order By: Relevance
“…Río Agrio originates as a natural acidic river due to the volcanic gases (H 2 SO 4 , HF, HCl) discharged by the hot springs that give it origin [30]. In this study, the pH measured at the origin (samples VA1 and VA2) was two (our group had measured pH values close to 1 in other campaigns [10]) and it remains almost constant all through the course of URA, in spite of the dilution effect produced by receiving multiple neutral tributary courses mainly of snowmelt origin. The dilution of URA after the origin is reflected in a decrease in conductivity, anions, and cations concentrations that starts in AS1 and becomes more drastic in CC.…”
Section: Influence Of Geochemistry Of the Río Agrio In Its Prokaryotimentioning
confidence: 52%
See 1 more Smart Citation
“…Río Agrio originates as a natural acidic river due to the volcanic gases (H 2 SO 4 , HF, HCl) discharged by the hot springs that give it origin [30]. In this study, the pH measured at the origin (samples VA1 and VA2) was two (our group had measured pH values close to 1 in other campaigns [10]) and it remains almost constant all through the course of URA, in spite of the dilution effect produced by receiving multiple neutral tributary courses mainly of snowmelt origin. The dilution of URA after the origin is reflected in a decrease in conductivity, anions, and cations concentrations that starts in AS1 and becomes more drastic in CC.…”
Section: Influence Of Geochemistry Of the Río Agrio In Its Prokaryotimentioning
confidence: 52%
“…At the beginning, we relied only on culture depending techniques which allowed the identification of several acidophilic iron and/or sulfur oxidizing species [32,33]. These results encourage us to perform more comprehensive assessments of prokaryotic biodiversity, such as cloning and sequencing of 16S rRNA genes of bacteria and archaea [10]. Despite finding a quite rich extreme biodiversity, both approaches were highly incomplete in the light of next-generation sequencing techniques.…”
Section: Characteristics Of the Prokaryotic Community Of The Copahue mentioning
confidence: 99%
“…The constant volcanic activity has determined the acidic, sulfur-rich, and high-temperature environments found in Copahue, such as Río Agrio and the geothermal springs (1, 2). Biodiversity studies done in Copahue (3, 4) revealed the presence of acidophilic bacteria and archaea, some of which are capable of growing at a high temperature and of using iron or sulfur compounds as energy sources. The detection of these extremophiles, most of which are yet uncharacterized and apparently autochthonous, makes Copahue a rich source of novel species with potential applications in biotechnological processes, mainly those related to biomining.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Caviahue-Copahue system is characterised by the presence of acidic hot springs that are a potential source of extremophilic microorganisms, many of them not yet discovered. This volcanic geothermal area has been studied in its geology, geochemistry, volcanism and thermalism over the past 20 years [5,9,11,21,22,35] and more recently its prokaryotic biodiversity has been assessed [3,4,34]. However, no new indigenous extremophilic species have been reported yet from this area.…”
Section: Introductionmentioning
confidence: 98%